DISTRIBUSI DAN PRODUKTIVITAS TENAGA KERJA USAHATANI SAWI (Brassica juncea L.) DI KELURAHAN LANDASAN ULIN UTARA KECAMATAN LIANG ANGGANG KOTA BANJARBARU - Yan Yosef Agus Suratman (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
The purpose of this study were (1). to gain an overview of aquaculture farming mustard; (2). to determine the costs and revenues on a large farm mustard; (3). to determine the distribution of labor cost and productivity of labor costs in the farming village of mustard in Middle of North Ulin villages. The method used in this study is a survey method by observation, where the technique of sampling  is done by Simple Random Sampling, out of a population of 80 farmers eggplant taken 38% in order to obtain 30 respondents. The results showed that farm production amounted to 1290.30 mustard belt / respondents or 322,575Kg / respondent (750.17 kg / ha). The average total cost of Rp. 3,000,192.98 / respondents or Rp. 6,977,053.44 / ha and receiving an average of Rp. 3,870,900.00 / respondents or Rp. 9,002,093.02 / ha. The distribution of farming activities, namely mustard land management, a raised bed, planting, maintenance and harvesting. The outpouring labor on land preparation activities HKO 7.73. Value distribution labor costs amounted to 50.88% and Productivity Index (IP) Rp. 126,790.04 / HKO greater than the rate of wage labor (Rp. 50.000,00 / HKO), means the use of labor in mustard farming in this areais productive or efficient.